Impaired spatial memory and enhanced long-term potentiation in mice with forebrain-specific ablation of the Stim genes - Garcia-Alvarez, Gisela; Shetty, Mahesh S.; Lu, Bo; Yap, Kenrick A.; Oh-Hora, Masatsugu; Sajikumar, Sreedharan; Bichler, Zoe; Fivaz, Marc (Frontiers in Behavioral Neuroscience, 2015)
Recent findings point to a central role of the endoplasmic reticulum resident STIM (Stromal Interaction Molecule) proteins in shaping the structure and function of excitatory synapses in the mammalian brain. The impact of the Stim genes on cognitive functions remains, however, poorly understood. To explore the function of the Stim genes in learning and memory, we generated three mouse strains with conditional deletion (cKO) of Stim1 and/or Stim2 in the forebrain. Stim1, Stim2 and double Stim1/Stim2 cKO mice show no obvious brain structural defects or locomotor impairment. Analysis of spatial reference memory in the Morris water maze revealed a mild learning delay in Stim1 cKO mice, while learning and memory in Stim2 cKO mice was undistinguishable from their control littermates. Deletion of both Stim genes in the forebrain resulted, however, in a pronounced impairment in spatial learning and memory reflecting a synergistic effect of the Stim genes on the underlying neural circuits. Notably, long-term potentiation (LTP) at CA3-CA1 hippocampal synapses is markedly enhanced in Stim1/Stim2 cKO mice and is associated with increased phosphorylation of the AMPA receptor subunit GluA1, the transcriptional regulator CREB and the L-type Voltage-dependent Ca2+ channel Cav1.2 on protein kinase A (PKA) sites. We conclude that STIM1 and STIM2 are key regulators of PKA signaling and synaptic plasticity in neural circuits encoding spatial memory. Our findings also reveal an inverse correlation between LTP and spatial learning/memory and suggest that abnormal enhancement of cAMP/PKA signaling and synaptic efficacy disrupts the formation of new memories.